ANALISIS PENGARUH PELATIHAN,MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Rumbewas, Cornelia; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2016)
The quality of human resources professionals are closely related to the performance of employees in a company. The ability of qualified employees will produce good employee performance anyway. Training, motivation, and disciplined work rated as the crucial factor because if it gets attention and do well, the positive impact on improving the quality of human resources or employee performance.       The purpose of this study was to analyze the effect of training, motivation and discipline on the performance of employees in the Regional Office of Bank BRI in Jayapura. Samples are 70 respondents and using purposive sampling techniques. Data analysis method used is multiple linear regression method with SPSS 23. Based on the results of this research show that the variables of training, motivation and discipline of work positively influence employee performance variables.